Fire & ice - Steele, Michael Anthony (New York : Scholastic, 2006)
When Bloom loses her Dragon Fire to Icy, Darcy, and Stormy, she feels like an ordinary Earth girl, just when she needs her powers most.
Based on the television series, Winx club.
Keywords: Fairies; Witches; Magic